Adjuvants Enhancing Cross-Presentation by Dendritic Cells: The Key to More Effective Vaccines? - Ho, Nataschja I.; Huis in 't Veld, Lisa G. M.; Raaijmakers, Tonke K.; Adema, Gosse J. (Frontiers in Immunology, 2018)
Over the last decades, vaccine development has advanced significantly in pursuing higher safety with less side effects. However, this is often accompanied by a reduction in vaccine immunogenicity and an increased dependency on adjuvants to enhance vaccine potency. Especially for diseases like cancer, it is important that therapeutic vaccines contain adjuvants that promote strong T cell responses. An important mode of action for such adjuvants is to prolong antigen exposure to dendritic cells (DCs) and to induce their maturation. These mature DCs are extremely effective in the activation of antigen-specific T cells, which is a prerequisite for induction of potent and long-lasting cellular immunity. For the activation of CD8+ cytotoxic T cell responses, however, the exogenous vaccine antigens need to gain access to the endogenous MHCI presentation pathway of DCs, a process referred to as antigen cross-presentation. In this review we will focus on recent insights in clinically relevant vaccine adjuvants that impact DC cross-presentation efficiency, including aluminum-based nanoparticles, saponin-based adjuvants, and Toll-like receptor ligands. Furthermore, we will discuss the importance of adjuvant combinations and highlight new developments in cancer vaccines. Understanding the mode of action of adjuvants in general and on antigen cross-presentation in DCs in particular, will be important for the design of novel adjuvants as part of vaccines able to induce strong cellular immunity.